2020
DOI: 10.3390/diagnostics10090683
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Parameters, Glucose and Lipid Profiles, and Thyroid Hormone Levels in Schizophrenia Patients with or without Metabolic Syndrome

Abstract: In this study, we aim to investigate associations between body fat parameters, glucose and lipid profiles, thyroid-stimulating hormone (TSH), and thyroid hormones (THs) levels in Tomsk-region schizophrenia patients depending upon the presence or absence of metabolic syndrome (MetS). A total of 156 psychiatric inpatients with schizophrenia who had been treated with antipsychotics for at least six months before entry were studied: 56 with and 100 without MetS. Reference groups consisted of general hospital inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Strengths of our study include excluding any history of cardiometabolic disease, including diabetes, hypertension, dyslipidaemia, and ischaemic heart disease. Our results contrast with studies using body impedance measures, which have reported significant increases (6) or decreases (7) in visceral body fat in schizophrenia. Differences in patient selection and matching, sample size, and differences in measurement technique may account for the differences in results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Strengths of our study include excluding any history of cardiometabolic disease, including diabetes, hypertension, dyslipidaemia, and ischaemic heart disease. Our results contrast with studies using body impedance measures, which have reported significant increases (6) or decreases (7) in visceral body fat in schizophrenia. Differences in patient selection and matching, sample size, and differences in measurement technique may account for the differences in results.…”
Section: Discussioncontrasting
confidence: 99%
“…MR studies have reported no significant difference in visceral fat content between cases and controls 3 (8-10), whereas studies using BIA have shown both increases (6) or decreases (7) in visceral fat in schizophrenia. However, studies measuring visceral fat using MRI tend not to measure total body fat content, and it is unclear whether these studies are able to detect differences in distribution at the whole body level in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, studying the contribution of 5-HT neurotransmission in the mechanisms of MetS can be considered a logical next step. However, due to the complex involvement of genuine metabolic as well as endocrine, immunological, and behavioral mechanisms [ 46 , 47 , 48 , 49 , 50 ], body weight is also considered in this study.…”
Section: Introductionmentioning
confidence: 99%